Predictors of biospecimen donation in the Black Women’s Health Study - Adams-Campbell, Lucile L. (Cancer Causes Control, 2016)
PURPOSE: Although African-Americans experience higher cancer morbidity and mortality rates compared to their White counterparts, their participation in biospecimen research is lower than that of their white peers. This study investigated the prevalence and predictors of biospecimen donation in a large, cohort study of Black women. METHODS: The BWHS is a follow-up study of U.S. Black women aged 21–69 years enrolled through postal health questionnaires. Between January 2004 and December 2007, participants were sent a consent form with a postage-paid return envelope, and a mouthwash collection kit. Univariate and age- and educational status-adjusted logistic regression models were used to estimate the association of socio-demographic, lifestyle and medical factors with donation of biospecimens. RESULTS: Buccal cells with consent forms were obtained from 26,790 women, for a response rate of 51 %. The strongest predictors of biospecimen donation were age: response increased from 48.6 % among those aged <40 to 63.1 % among those aged 60 and older [RR 1.30 (95 % CI 1.27, 1.34)]; multivitamin use [RR (95 % CI) 1.32 (1.30, 1.34)]; physician visit in the previous 2 years [RR (95 % CI) 1.61 (1.58, 1.65)], and a history of breast [RR (95 % CI) 1.59 (1.56, 1.63)], colon [RR (95 % CI) 1.18 (1.16, 1.20)], and cervical [RR (95 % CI) 1.63 (1.60, 1.67)] cancer screening. CONCLUSIONS: We found that 51 % of women in the geographically-dispersed Black Women’s Health Study cohort were willing to provide mouthwash samples to be used for genetic analyses. The response in this study is encouraging given published findings of low overall participation rates of African-Americans in genetic studies.